Amylase-Producing Maltooligosaccharide Provides Potential Relief in Rats with Loperamide-Induced Constipation. (27th August 2020) - Jang, Eun Yeong; Ahn, Yejin; Suh, Hyung Joo; Hong, Ki-Bae; Jo, Kyungae
Abstract : Constipation is a chronic disease caused by infrequent, inadequate, and difficult bowel movements. The present study aimed to evaluate the potential laxative effect of maltooligosaccharide (MOS) on loperamide-induced constipation in a rat model. In vitro experiments were conducted to evaluate the effect of MOS on the growth of lactic acid bacteria. Moreover, to examine the effect of MOS administration on Sprague-Dawley (SD) rats with loperamide-induced constipation, the drinking water for the rats was supplemented with 10% or 15% of MOS for 14 days, and, thereafter, the improvement in constipation was assessed. For this, the rats were divided into five groups: normal (Nor), loperamide-induced constipated (Con), positive control (15% of dual-oligosaccharide (DuO-15)), 10% MOS treated (MOS-10), and 15% MOS-treated (MOS-15). In an in vitro test, MOS treatment promoted the growth of lactic acid bacteria except Lactobacillus bulgaricus . Treatment with higher MOS dose relieved constipation in rats by improving the fecal pellet and water content. Furthermore, in the high MOS dose group, the cecal short-chain fatty acid levels significantly increased compared to those in the control group (P < 0.001 ). MOS treatment also improved the mucosal thickness as well as mucin secretion and increased the area of intestinal Cajal cells compared to that in the control group (P < 0.001 ). These findings suggest that MOS relieves constipation and has beneficial effect on the gastrointestinal tract, and, therefore, it can be used as an ingredient in functional foods for treating constipation or improving intestinal health.